Comparison of Marginal Bone Loss Around Titanium and Zirconia Implants: Clinical Trial in Cameroon and Belgium. - Jules Julien Ndjoh; Georgette Marina Allou Amoin; Mengong Moneboulou Hortense; Sandra lydie Akena Ndeng; N’goran Justin Koffi; Charles Bengondo Messanga (HEALTH SCIENCES AND DISEASE, 2023)
Introduction. In addition to the success of titanium implants since Branemark, several researchers report effects observed on the adjacent implant tissues. The interactions between these tissues and the implant depend on the type of biomaterials, the characteristics of the individual and the environment. The objective of our study was to compare bone resorption around titanium and zirconia implants in two groups of melano-African and European leukoderma patients. Methods. A randomized, single-blind clinical trial was conducted in 28 patients with bilateral mandibular intercalary edentulism, 26 implants in Cameroon and 30 in Belgium. The procedure consisted of the placement of one titanium and one zirconia dental implant on each hemi-arch. Bone resorption was evaluated by the variations of mesial and distal crete heights measured with the Cone Beam at 06, 12 and 18 months. Results. At 18 months, mesial (p=0.004) and distal (p=0.046) bone resorption around titanium implants was greater in melano-African patients. These results are similar in European leukoderma patients, p=0.010 mesially and p=0.010 distally. The comparison of patients according to their origin showed less distal bone resorption in the Cameroon group (p=0.001). Conclusion. Bone resorption at 18 months around titanium and zirconia implants is less important in melano-African patients. These results may allow a better choice for implant durability in Africa in the long term.